Pengaruh Sikap Resiliensi Pada Masa Pandemi Covid-19 Terhadap Kemampuan Akademik Mahasiswa Pada Mata Kuliah Evaluasi Pedidikan - muhamad sukri situmeang; Syamsudin Kastoer (Sekolah Tinggi Agama Islam Publisistik Thawalib Jakarta, 2020)
The aims of this study was to determined the influence of resilience attitudes during the covid-19 pandemic on student academic abilities in Learning Evaluation course. This research is based on low academic achievement of students in evaluation of learning course. Students find difficulty and easily give up in solving the problem. The method used in this research is survey method with correlation technique sampling. Population in this research is all student in study program of Islamic Education, STAI Thawalib Jakarta. Research sample is taken by purposive sampling technique as many as 17 students who take learning evaluation course. The Instruments in this study are test description of academic ability questions and non test questions in the form of attitude of resilience scale. The results showed that there was a positive influence between resilience attitudes and student academic ability, with resilience attitudes influence of 59,4% to student academic ability and 40,6% by other variable.